Networks of Life: A Jungian reading about aging and death - Magalhães, Gilzete Passos; Gonçalves, Giselli Renata; Sawaguchi, Glaucia; Taba, Sheila; Faria, Durval Luiz de (Revista Kairós-Gerontologia, 2014)
This work aims at proposing an approach of the stages of aging and dying within the individuation process, starting from the symbolic amplification of images of these phases of life in light of Analytical Psychology. For the purpose of correlating these images with the stages of human development, particularly with the phases of the end of maturity and closing of the life cycle, a study on imagery and bibliography of aging and dying was conducted based on the theoretical framework of Analytical Psychology and of Post-Jungian authors. To that effect, the symbolic amplification of images taken from the plastic arts, literature, religion and mythology was made. The results of the study indicated that the death-related images bear a relationship with the individuation process, which points out to the need to explore this topic – which is a taboo in contemporary society – in a creative and significant manner; something that was synthesized by Jung himself in the expression “to die with life”.